Pengaruh Media Sosial terhadap Kepedulian Zakat Mahasiswa: Moderasi oleh Literasi Zakat - Ismitaniar, Nuriska Afifa; Malik, Ifda Suyyuti; Kholmi, Masiyah (ZAWA: Management of Zakat and Waqf Journal, 2025)
This study aims to analyze the influence of social media on students’s zakat awareness with zakat literacy as a moderating variable. The research was conducted on 85 students of the Faculty of Economics and Business in one of the university in Malang who actively use social media and have been exposed to zakat content. The study employed a quantitative approach with Structural Equation Modeling (SEM) analysis technique based on Partial Least Squares (PLS). The results showed that social media had a positive and significant effect on students' zakat awareness with a p-value of p=0.006 (p < 0.05). This shows that the more often students access zakat information on social media, the greater their awareness of zakat obligations will become. However, zakat literacy is not proven to significantly moderate the relationship between social media and zakat awareness, with a p-value of p=0.505 (p > 0.05). This finding indicates that the effect of social media on zakat awareness is direct and does not depend on the level of zakat literacy. This study recommends that zakat content on social media should be presented in an interesting, educational, and socially relevant way that resonates with students' lives.